Family matters - Mistry, Rohinton (Faber and faber, 2002)
"The setting is Bombay, mid-1990s. Nariman Vakeel, suffering from Parkinson's disease, is the elderly patriarch of a small, discordant family. In a building called Chateau Felicity, he and his two middle-aged stepchildren - Coomy, bitter and domineering, and her just-younger brother, Jal, mild mannered and acquiescent - occupy a once-elegant apartment whose ruin is progressing as rapidly as Nariman's disease.